Efficient class of ratio cum median estimators for estimating the population median. - Mir Subzar; Showkat Ahmad Lone; Emmanuel J Ekpenyong; Abdul Salam; Muhammad Aslam; T A Raja; Salmeh A Almutlak (PLoS ONE, 2023)
In estimation theory, the use of auxiliary information significantly improves precision while estimating population parameters. In this paper, an efficient class of ratio cum median estimators of the population median is suggested using simple random sampling without replacement. The expressions for bias and mean square error of the proposed class are derived theoretically. The condition for the asymptotic optimum estimator is obtained with its bias and mean square error expressions. Under certain realistic conditions, the asymptotic optimum estimator is more proficient, based on analytical and numerical comparisons with some existing estimators that are members of the suggested class of estimators. The superiority of the proposed ratio cum median estimators is shown through real data applications. Such a new proposed estimator will be useful in the future for data analysis and making decisions.